2016
DOI: 10.1016/j.rboe.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of femoroacetabular impingement using controlled hip dislocation after occurrence of slipped capital femoral epiphysis

Abstract: ObjectiveTo present our experience and preliminary results from using controlled hip dislocation to treat cam-like femoroacetabular impingement, in teenagers and young adults with sequelae of slipped capital femoral epiphysis.MethodsThis was a retrospective analysis on 15 patients who were treated in a tertiary-level hospital between 2011 and 2013. The following data were collected for analysis from these patients’ files: demographic data, surgical procedure reports, joint mobility evaluations, patients’ perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Likewise, patients with mild, stable slips may present years after SCFE onset, without previously seeking treatment. Osteochondroplasty through controlled surgical hip dislocation, as originally described by Ziebarth et al [33], has been found in short-term follow-up studies to improve joint mobility, hip pain, and radiographic alpha angles in patients with FAI who have a history of SCFE [2,30]. One major advantage of this approach is that intertrochanteric osteotomy may be performed concomitantly, if necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, patients with mild, stable slips may present years after SCFE onset, without previously seeking treatment. Osteochondroplasty through controlled surgical hip dislocation, as originally described by Ziebarth et al [33], has been found in short-term follow-up studies to improve joint mobility, hip pain, and radiographic alpha angles in patients with FAI who have a history of SCFE [2,30]. One major advantage of this approach is that intertrochanteric osteotomy may be performed concomitantly, if necessary.…”
Section: Introductionmentioning
confidence: 99%